The Effect of a Social Cognitive Theory-based Educational Intervention on the Physical Activity of Female Adolescents - Hossein Shirvani; Hormoz Sanaeinasab; Reza Tavakoli; Mohsen Saffari; kazem Khalaji; Sara Me'mar (Iranian Association of Health Education and Health Promotion, 2017)
Background and objective: Reports have revealed a growing tendency towards sedentary lifestyles in all age groups, especially among female adolescents. This study aimed to determine the influence of a social cognitive theory (SCT)-based educational intervention on the physical activity of secondary school students in 2013. Materials and methods: This randomized, controlled field trial was conducted on 132 second- and third-year high school female students. The subjects were divided into control and intervention groups- 68 students with an average of 13 ± 1 years of age in each group. Data collection tools included demographic, physical activity, and SCT-based questionnaires. For data analysis, descriptive statistics were calculated and regression test was performed using SPSS 22 through descriptive statistics and multiple linear regression with 95% confidence interval. Results: In the intervention group, a significant increase was observed in the mean scores of selected SCT concepts (environmental factors, behavioral capacity, outcome expectation, expectancies, observational learning, reinforcement, and self-efficacy), affecting physical activity (p < 0.001). Multiple linear regression in the intervention group showed that daily and weekly physical activity increased to 70.14 and 263.34 minutes, respectively. Conclusion: SCT-based educational intervention has a positive impact on the physical activity of female adolescents. Paper Type: Research Article.